Characteristics and Clinical Outcomes of Open Surgery for Trigger Digits in Diabetes - Ho, Sean Wei Loong; Chia, Ching Yee; Rajaratnam, Vaikunthan (Journal of Hand and Microsurgery, 2019)
Introduction Trigger digit is a common condition of the hand. Diabetes has a known association with the development of trigger digit. It is thought to influence the clinical presentation and efficacy of open surgical release. This study aimed to assess the differential characteristics of trigger digits and the clinical outcomes of open surgery for trigger digits in diabetics.Materials and Methods This was a retrospective study of all patients who underwent open surgical release of trigger digits in a single institution from 2012 to 2013. Patients were divided into two groups with group 1 consisting of all patients with a history of diabetes. Group 2 consisted of all patients without diabetes. Demographics and clinical presentation were reviewed. All patients were reviewed via a telephone questionnaire at least 2 years after the initial surgery and were assessed for patient-reported outcomes.Results There were 201 patients who met the inclusion criteria, of which 191 patients were recruited. This included 87 (45.5%) males and 104 (54.5%) females. A total of 260 open releases were performed. Sixty-one (31.9%) patients were diabetic, and 130 (68.1%) patients were nondiabetic. The diabetic group was significantly older than the nondiabetic group (p = 0.002). The dominant hand was not significantly more affected than the nondominant hand (p = 0.51). The middle finger was most commonly involved (43.5%), and the little finger was the least commonly involved (1.2%). There was no significant increase in multiple-digit presentation in the diabetic population when compared with the nondiabetic population (p = 0.52). There was a low complication rate and a high rate of postoperative satisfaction after open surgery in both groups.Conclusion Diabetes does not predispose patients to increased rates of multiple trigger digit presentation or increased clinical severity on presentation. Open surgery for trigger digit is an effective and safe treatment modality for diabetics.
Keywords: trigger; open release; diabetes